Correctional management and the law: a penological approach - Gideon, Lior (Carolina Academic Press, 2017)
Introduction : the goals of punishment and aims of correctional institutions -- Historical account of correctional law -- The administration of probation and parole -- Jail and prison administration -- First amendment : freedom of speech -- First Amendment : freedom of religion -- Fourth amendment : search and seizure -- Due process and other associated rights -- Eighth amendment : physical aspects of punishments -- Eighth amendment : conditions of confinement -- Access to federal courts -- Community supervision and the law : probation and parole -- Law and incarcerated offenders with special needs -- United States Constitution and its relevance to correctional management -- Conclusion : the importance of judiciary involvement in correctional management